Strategi Penyelamatan Muka melalui Kesantunan Berbahasa dalam Komunikasi Umat Hindu di Karangasem - Ni Kadek Juliantari (Jayapangus Press, 2019)
This study aims to describe the manifestation of the politeness of the movement used as a salvation goal in the Hindu communication era in Karangasem, describing the communication strategy through politeness in Hindu communication in Karangasem, and describing efforts to maintain politeness in Hindu communication. The collected data were analyzed using the Miles and Huberman flow model, starting from data, data reduction, data presentation, and verification and conclusion reduction.The results in this study indicate that (1) face-saving strategy through language politeness in communication of Hindus in Karangasem is carried out through fulfillment of politeness maxim/conversation maxim (which includes wisdom maxim, generosity maxim, praise/appreciation maxim, maxim of humility, maxim of agreement/approval, and maxim of conciliation), avoidance of taboo words, use of euphemisms, and use of honorifics (forms of respect). (2) The use of advance rescue strategies through politeness in this language can have positive and negative implications for Hindus in Karangasem. The positive implication is the creation of living harmony in the community, mutual respect between people, avoiding social tensions that may occur in the context of society, strengthening the peaceful behavior of the brethren, preserving the concept of paras paros sarpanaya, and suppressing the occurrence of offense among communication actors. Meanwhile, the negative implications are the emergence of a culture of not being forthright in order to safeguard the feelings of others. (3) The efforts that can be done to maintain or advance this language politeness are the presence of a culture of good manners among Hindus in Karangasem, the existence of Awig-awig in the village which regulates the Sukerta Tata Pawongan, and the existence of Balinese language instructors entering the village in charge of fostering the community and village manners, as well as efforts to foster positive attitudes of speakers towards their language.